2018
DOI: 10.3390/ijerph15051002
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Daily Living and Determinant Factors among Older Adult Subjects with Lower Body Fracture after Discharge from Hospital: A Prospective Study

Abstract: Fracture is a type of musculoskeletal injury that contributes to an inability to perform daily activities. The objective of this study was to evaluate activities of daily living (ADL) of older adult patients with lower body fracture and to determine factors influencing ADL. Patient’s ADL was assessed at pre-fracture, ward admission and post-discharge phases using the Katz ADL questionnaire. There were 129 subjects at pre-fracture and ward phases and 89 subjects at discharge phase. There were four independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
0
10
0
2
Order By: Relevance
“…Even little changes in the ADL function could lead to poor clinical outcomes [30][31] . ADL functional status has been shown to be an independent predictor of mortality in heterogeneous populations [7][8][9][10][11] . In CAP, a worse ADL is directly related to increased immediate and long-term mortality [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even little changes in the ADL function could lead to poor clinical outcomes [30][31] . ADL functional status has been shown to be an independent predictor of mortality in heterogeneous populations [7][8][9][10][11] . In CAP, a worse ADL is directly related to increased immediate and long-term mortality [32] .…”
Section: Discussionmentioning
confidence: 99%
“…ADL functional status decline can lead to adverse clinical outcomes in pulmonary infections, dementia [7] , heart failure [8] , hip fractures [9][10] , and acute medical patients [11] . The baseline ADL functional status may be one of the determinants for the evolution of pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…The Katz Activities of Daily Living (ADL) scale is an instrument that developed to assesses six primary and psychosocial functions: bathing, dressing, going to toilet, transferring, feeding, and continence ( Ibrahim 2018 ). Katz and collaborators found that these six activities have a hierarchical order in which the most complex functions are lost first.…”
Section: Methodsmentioning
confidence: 99%
“…The data was collected using pretested and structured questionnaire. The structured questionnaire was adopted by an extensive review of related studies, 11 , 16 , 18 WHO's trauma surveillance questionnaire, 19 and LEFS questionnaire. 15 The questionnaire, which included domains like socio-demographic characteristics: age, gender, occupation; medical comorbidity, behavioral characteristics; and fracture-related characteristics, including types of fracture management, types of fracture, and duration of hospitalization.…”
Section: Methodsmentioning
confidence: 99%